PERAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA GENERASI MUDA - Johan Sidebang; Monica sinaga; Axido sihombing; Dio Hutasoit; Patricia Herpayanti Rajagukguk; Nalom Siagian (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Interest is a desire or feeling of attraction to something that a person wants to do without any coercion and based on their personal desires. Interest will motivate someone to achieve something. Many factors influence students' interest in entrepreneurship, including social media, entrepreneurial knowledge, and self-confidence. The purpose of this study was to determine the influence of social media, entrepreneurial knowledge, and self-confidence on the entrepreneurial interest of the younger generation. Data collection used a systematic review by analyzing research manuscripts obtained from Google Scholar indexed nationally and internationally over the past five years. The results of this study indicate that social media has a positive and significant influence on entrepreneurial interest, entrepreneurial knowledge has no significant influence on entrepreneurial interest, self-confidence has a positive and significant influence on entrepreneurial interest, and social media. Entrepreneurial knowledge and social media jointly influence entrepreneurial interest in the younger generation.